Algorithms For Multi-Criteria Global Path Planning Of An Unmanned Combat Vehicle - Saw Hin, Saw Veekeong (2020)
Unmanned combat vehicle (UCV) is an armed robotic driverless vehicle deployed in modern warfare to reduce the casualties of safety personnel in dangerous missions. An important aspect in the development of UCV is its path navigation capability. In this research, we consider the global path planning (GPP) problem of the UCV with three attributes: traverse time, risk level, and signal jamming level.